Collaborative Governance In The Reduction Of Earthquake And Tsunami Disaster Risks In Bengkulu City - Sri Indarti; Juim Juim (Iapa Proceedings Conference, 2018)
This study analyzes Collaborative governance in the earthquake and tsunami Disaster Risk Reduction Policy (DRR). Collaborative governance analysis in disaster risk reduction policy uses Ratner's Collaborative Governance Stages (2012) theory, which includes Identifying Obstacles and Opportunities, Debating Strategies for Influence and Planning Collaborative Actions Disaster Risk Reduction for Earthquake and Tsunami Disasters has been carried out in the City of Bengkulu which is located on the west coast of the island of Sumatra. Various institutions have developed DRR, with their respective patterns and limited coordination. Collaborative governance foundation has been carried out and needs to be developed strategically as an alternative implementation and development of more effective policies and management. The findings in this study that Collaboration on DRR The earthquake and tsunami in Bengkulu City were in the pilot stage, which provided the initial foundation for developing DRR policy implementation. There are obstacles in DRR implementation and management, which require strategic collaboration for the development of DRR effectively and equitably and continuously. Collaborative follow-up needs to be done with the establishment of a permanent forum that is needed flexibly, by avoiding a strict hierarchical structure or using organization horizontally, so that it can accommodate and utilize various stakeholders' potential optimally.